Assistive technology and people: a position paper from the first global research, innovation and education on assistive technology (GREAT) summit. (4th July 2018) - Desmond, Deirdre; Layton, Natasha; Bentley, Jacob; Boot, Fleur Heleen; Borg, Johan; Dhungana, Bishnu Maya; Gallagher, Pamela; Gitlow, Lynn; Gowran, Rosemary Joan; Groce, Nora; Mavrou, Katerina; Mackeogh, Trish; et al.
Abstract: Assistive technology (AT) is a powerful enabler of participation. The World Health Organization's Global Collaboration on Assistive Technology (GATE) programme is actively working towards access to assistive technology for all. Developed through collaborative work as a part of the Global Research, Innovation and Education on Assistive Technology (GREAT) Summit, this position paper provides a "state of the science" view of AT users, conceptualized as "People" within the set of GATE strategic "P"s. People are at the core of policy, products, personnel and provision. AT is an interface between the person and the life they would like to lead. People's preferences, perspectives and goals are fundamental to defining and determining the success of AT. Maximizing the impact of AT in enabling participation requires an individualized and holistic understanding of the value and meaning of AT for the individual, taking a universal model perspective, focusing on the person, in context, and then considering the condition and/or the technology. This paper aims to situate and emphasize people at the centre of AT systems: we highlight personal meanings and perspectives on AT use and consider the role of advocacy, empowerment and co-design in developing and driving AT processes.